(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
In this work we propose to review the category field of Human Rights, widely used in memory studies in recent years, based on the analysis of the case of the Memory Park – Monument to the Victims of State Terrorism (Parque de la Memoria – Monumento a las Víctimas del Terrorismo de Estado in Spanish). For this, first, we will make a brief introduction to the notion of social fields developed by the sociologist Pierre Bourdieu. Then we will review the field category of field of Human Rights and its main characteristics. Thirdly, we will return to some of the works that previously conceived the Memory Park in light of the category of field of Human Rights. And finally, based on an analysis of the management spaces of this memory site and the trajectories of its workers and the people who were in charge of its management, we will see how the category of field of Human Rights continues to be useful for thinking about the spaces linked to the demands for Memory, Truth and Justice.